A case study of preloading in peat using finite element method with plaxis software - Amanda, anak Mangan. (Universiti Malaysia Sarawak (UNIMAS), 2010)
Peat is categorized as problematic soil because it has low shear strength and high compressibility, which are not suitable for construction. Peat covers 13% of Sarawak land where most major roads are constructed. Therefore, it is necessary to find suitable alternatives to improve the strength since nowadays lands are very expensive and very limited. Preloading using sand has been a popular technique of peat ground improvement for road sub base in Sarawak. This study presents the effect of pre loading in peat using finite element method using PLAXIS software to model stage construction of a preloading embankment and associated consolidation settlement and pore pressure dissipation characteristics. Two cases are generated with differences in the boundary conditions and compared while using the same material properties, stage of constructions and consolidation analyses as well as coarseness mesh in a plain strain model. From the cases analyzed, it is clear that the pore pressure disperses with open boundary condition at the bottom of peat, and the rate consolidation settlement faster compared to the case where closed boundary condition at the bottom of peat. In conclusion, the pore pressure will disperse provided there is open boundary condition and it does not lead to large difference in consolidation settlement, and different coarseness in the sub base mesh generation will give different failure mechanism. Therefore, real parametric of peat properties should be used for future research.